The Impact of Anatomy Learning Using Cadaver in Nursing Students - Burm , Eunae; Gu, Jeung-Ah (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The purpose of this study was to investigate the change of perception of nursing students due to the education using cadaver. Methods/Statistical analysis: We analyzed a group of 60 second-year nursing students before and after attending the cadaver practice. Each sheet contained demographic questions, a visual analog scale on stress(VAS), Interest in anatomy, changes in attitude statement and Emotional response to the dissection after anatomy learning using cadaver. We analyzed the collected data in terms of frequency, percentage, mean and standard deviation. All statistical analyses were carried out using SPSS software version 23. Findings: The results were mostly positive as students stated the lectures ‘helped to understand the body structure’ and influenced them to become ‘interested in anatomy’. In addition, there were many students who wished to participate again in anatomy learning using cadaver. It has also been found that lectures with bodies increase students’ interest and understanding of anatomy learning and positively affect their emotional attitudes. Improvements/Applications: We suggest that anatomical studies for nursing students should have a separate curriculum with the body.